Problemas en el cultivo de la yuca - Lozano, J.C.; Bellotti, Anthony C.; Reyes, J.A.; Howeler, Reinhardt H.; Leihner, D.E.; Doll, J. (International Center for Tropical Agriculture, 1981)
Information on some diseases and pests that attack cassava, as well as the symptoms induced by nutritional deficiencies and toxicities and damage resulting from the misuse of herbicides are given in this manual. Specific and general recommendations regarding the control of the described problems are included. Disease control on a commercial scale is discussed. Formulae suggested for stake treatment before planting and storage and a key for identifying some cassava diseases are annexed. Color photos on symtomatology are included. (AS)